INDUSTRY 4.0: SMART PRODUCTION EQUIPMENT (British Journal of Global Ecology and Sustainable Development, 2023)
The article substantiates the use of smart production equipment, which is the basis of Industry 4.0. The emphasis is on software that controls the operation of not one installation, but a group of machines and systems as a whole.